How populist attitudes scales fail to capture support for populists in power - Jungkunz, Sebastian; Fahey, Robert A.; Hino, Airo (PloS one, 2021)
Populist attitudes are generally measured in surveys through three necessary and non-compensatory elements of populism, namely anti-elitism, people-centrism, and Manicheanism. Using Comparative Study of Electoral Systems Module 5 (2016–2020) data for 30 countries, we evaluate whether this approach explains voting for populist parties across countries in Asia, Europe and the Americas. We show that the existing scales of populist attitudes effectively explain voting for populists in countries where populist leaders and parties are in opposition but fail to explain voting for populist parties in countries where they are in power . We argue that current approaches assume “the elite” to mean “politicians”, thus failing to capture attitudes towards “non-political elites” often targeted by populists in office—in particular, journalists, academics/experts, bureaucrats, and corporate business leaders. The results reveal limits to the usefulness of existing survey batteries in cross-national studies of populism and emphasize the need to develop approaches that are more generalizable across political and national contexts.